The Effect of Profitability, Solvency, And Systematic Risk on Stock Returns with Moderating Variables by Audit Quality - Satish Verenathan; Harsono Yoewono (Profesional Muda Cendekia Publishing, 2023)
Return is one of the factors that motivate investors to invest and is also a reward for the courage of investors to take risks on the investments made. Stock returns are influenced by three factors, namely internal factors, external factors and market factors. This study aims to determine the profitability, solvency, and systematic risk variables affect stock returns with moderating variables by audit quality. This study uses a quantitative approach. The population in this study is companies engaged in the mining sub-sector in Indonesia in 2011 – 2020 which are listed on the Indonesia Stock Exchange (IDX) or the Indonesia Stock Exchange (IDX). The results in this study are that profitability and solvency have an effect on stock returns, systematic risk has no effect on stock returns, while the audit quality variable as a moderating variable strengthens the return on equity, debt equity ratio and systematic risk variables on stock returns in mining sub-sector companies listed in Indonesia Stock Exchange 2011-2020 period.